UJI DAYA HAMBAT JAMUR ENDOFIT AKAR BAKAU ACHANTUS TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS DAN ESCHERICHIAE COLI - Pongantung, Clara; Kepel, Billy; Bodhi, Widdhi (e-Biomedik, 2015)
Abstract: Fungi and bacteria are microbes that are classified in the general stage of Endofit. Fungi is the most isolated form of Endofit. To this point studies articulating endofit are still at a scarce stage, without a doubt the corresponding relationship between plants and organisms. Endosimbions are considered in a state between grass that grows endemic in The United States of America (truf grass) and endofit fungi, Neotyphodium SP. The purpose of these researches are to see and understand the inhibition of bacteria growth from endofit fungi that can be obtained from the roots of Mangrove Acanthus against bacteria Staphylococcus Aureus and Escherichia coli. These studies have been researched since November 2013 to January 2014 at the Biomedical Research Laboratory Faculty of Medicine University of Sam Ratulangi. The research results that were conjured from the Mangrove root type Achantus have an inhibitory effect on the test bacteria research, which are Staphylococcus Aureus and Escherichia Coli.Keywords: endofit fungi, Achantus, Staphylococcus Aureus, and Escherichia Coli.Abstrak: Jamurdan bakteri merupakan mikroba yang paling umum dijumpai sebagai endofit, sedangkan endofit yang paling sering diisolasi ialah jamur. Sejauh ini penelitian mengenaiendofit masih sanga tjarang dipelajari, akan tetapi hubungan antara tumbuhan dengan organisme endosimbion dapat dilihat antara suatu jenis rumput yang tumbuh endemik di Amerika Utara (truf grass) dengan jamur endofit Neotyphodium sp. Tujuan penelitian ini untuk melihat dan mengetahui daya hambat pertumbuhan bakteri dari jamur endofit yang terdapat pada akar mangrove Acanthus terhadap bakteri Staphylococcus aureus dan Escherichia coli. Penelitian ini dilakukan sejak bulan November 2013 sampai dengan Januari 2014 di Laboratorium Riset Biomedik Fakultas Kedokteran Universitas Sam Ratulangi. Dari hasil penelitian yang didapat akar mangrove jenis achantus memiliki daya hambat terhadap bakteri uji pada penelitian ini yaitu staphylococcus aureus dan Escherichia coli.Kata kunci: jamur endofit, Achantus, Staphylococcus aureus, Escherichiae coli.